Y-TZP zirconia regeneration firing: Microstructural and crystallographic changes after grinding - Ryan, Daniel Patrick Obelenis [UNESP]; Fais, Laiza Maria Grassi [UNESP]; Antonio, Selma Gutierrez [UNESP]; Hatanaka, Gabriel Rodrigues [UNESP]; Candido, Lucas Miguel [UNESP]; Pinelli, Ligia Antunes Pereira [UNESP] (Japanese Society for Dental Materials and Devices, 2017)
This study evaluated microstructural and crystallographic phase changes after grinding (G) and regeneration firing/anneling (R) of Y-TZP ceramics. Thirty five bars (Lava™ and Ice Zirkon) were divided: Y-TZP pre-sintered, control (C), regeneration firing (R), dry grinding (DG), dry grinding+regeneration firing (DGR), wet grinding (WG) and wet grinding+regeneration firing (WGR). Grinding was conducted using a diamond bur and annealing at 1,000°C. The microstructure was analyzed by SEM and the crystalline phases by X-ray diffraction (XRD). XRD showed that pre-sintered specimens contained tetragonal and monoclinic phases, while groups C and R showed tetragonal, cubic and monoclinic phases. After grinding, the cubic phase was eliminated in all groups. Annealing (DGR and WGR) resulted in only tetragonal phase. SEM showed semi-circular cracks after grinding and homogenization of particles after annealing. After grinding, surfaces show tetragonal and monoclinic phases and R can be assumed to be necessary prior to porcelain layering when grinding is performed.
Keywords: Surface analysis; Surface treatment; XRD (X-ray diffraction); Zirconia